Albania : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report, 2019)
Despite robust GDP growth, projected at 4 percent in 2018, inflation remains below its 3 percent target. The fiscal deficit has stabilized around 2 percent of GDP, implying a modest gradual reduction in public debt, which remains high at close to 70 percent of GDP. Monetary policy was relaxed further in June 2018 following a rapid appreciation of the exchange rate. The current account deficit has moderated over recent years, to about 6.5 percent of GDP. The outlook is mostly positive, with GDP growth projected to converge to 4 percent over the medium term, with inflation stabilizing around its target by 2021. Further fiscal consolidation and an accommodative monetary policy, combined with growth-promoting structural reforms represent the right policy mix.